(untitled) (Bangladesh Journal of Botany, 2023)
Information regarding additive and dominance properties of gene of the quantitative traits is very important to improve any crops. Five chickpea genotypes were taken as a base material for this study and five different crosses were made between the genotypes to raised F1, F2 and biparental (BIP’s) family. Analysis of variance showed significant differences among the families in almost all the cases. Higher magnitude of additive component than that of dominance component along with high narrow sense heritability and high genetic advance recorded for pod weight plant-1 in cross-4 and cross-5; number of seeds plant-1 in cross-3, cross-4 and cross-5; while seed weight plant-1 in cross-3 and cross-5. This is signifying that the selection of these traits for the respective crosses will be very effective for the improvement of chickpea yield. Regression item in some cases was significant which revealed good relationship between biparental families and their parents and vice-versa. Significant linkage in both coupling and repulsion phases were detected. Bangladesh J. Bot. 52(3): 731-739, 2023 (September)